Functional characterization of seven-band grouper immunoglobulin like cell adhesion molecule, Nectin4 as a cellular receptor for nervous necrosis virus. Issue 93 (October 2019) - Krishnan, Rahul; Qadiri, Syed Shariq Nazir; Oh, Myung-Joo
Abstract: Nectin-4/PVRL4 belonging to the family of immunoglobulin-like cell adhesion molecules was identified as a potential cellular receptor for several animal viruses. Here we show that nervous necrosis virus that causes viral nervous necrosis in teleosts uses the same receptor in its life cycle. Transfection of SSN-1 cell lines with an expression vector encoding Nectin-4 rendered them to be more susceptible to NNV. Immunofluorescence microscopy on Nectin-4 expressing cells revealed that the protein interacted with NNV specifically. A virus binding assay indicated that Nectin-4 was a bonafide receptor that supported virus attachment to the host cell whereas siRNA directed against Nectin-4 blocked NNV infections in grouper primary brain cells. Results of the present study will improve our understanding of the pathogenesis of NNV infection and provide a target for the development of novel antiviral interventions in marine finfish aquaculture. Highlights: PVRL4/Nectin-4 was identified as a receptor for NNV. Ectopic expression enhanced viral uptake and increased replication kinetics. NNV capsid interacted well with the Nectin-4 in assays. siRNA silencing restricted the viral entry and replication in the cells.